2017
DOI: 10.1002/prep.201700032
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Parameters of PBX Based on Cis‐1,3,4,6‐tetranitroocta‐hydroimidazo‐[4,5‐d] imidazole Obtained by Isoconversional Methods using Different Thermal Analysis Techniques

Abstract: The thermal decomposition kinetics of the interesting polycyclic nitramine cis-1, 3,4,6-tetranitrooctahydroimidazo-[4,5-d]imidazole (BCHMX) and its polymer bonded explosive (PBX) based on polyurethane matrix, have been investigated using different thermal analysis techniques and methods. The used polyurethane matrix is based on hydroxyl-terminated polybutadiene (HTPB) cured by hexamethylene diisocyanate (HMDI). Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were used nonisothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…As commonly suggested in literatures, the mean values of activation energy using OFW and KAS methods were calculated in the interval of (a ¼ 0.3-0.7) due to the large inuence of the experimental conditions specially in case of TG/DTG on the data quality of the process "tails". [47][48][49][50] Conclusions 2,2,2-Trinitroethyl-formate (TNEF) is a new interesting (chlorine-free) green high-energy dense oxidizer (HEDO), which can be easily prepared from 2,2,2-trinitroethanol (TNE). The burning characteristics calculated for the new green propellant formula based on TNEF with HTPB was higher than that of traditional propellant based on AP/HTPB.…”
Section: Resultsmentioning
confidence: 99%
“…As commonly suggested in literatures, the mean values of activation energy using OFW and KAS methods were calculated in the interval of (a ¼ 0.3-0.7) due to the large inuence of the experimental conditions specially in case of TG/DTG on the data quality of the process "tails". [47][48][49][50] Conclusions 2,2,2-Trinitroethyl-formate (TNEF) is a new interesting (chlorine-free) green high-energy dense oxidizer (HEDO), which can be easily prepared from 2,2,2-trinitroethanol (TNE). The burning characteristics calculated for the new green propellant formula based on TNEF with HTPB was higher than that of traditional propellant based on AP/HTPB.…”
Section: Resultsmentioning
confidence: 99%
“…The mean values of effective activation energy using OFW and KAS methods were calculated in the interval of (a = 0.3-0.7) as commonly suggested in literatures [13,14,20,40] due to the large influence of the experimental conditions specially in case of TG/DTG on the data quality of the process "tails". Figure 8 shows the relation between the pre-ex- Note: T ot : onset temperature of decomposition; T oe : onset temperature of the end decomposition; T i : initial thermal decomposition temperature; T p : the peak temperature of mass loss rate; Mass Loss: from initial temperature to end temperature of DTG peak 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 ponential factor A and the effective activation energy at each step of conversion and the effect of adding the oxidizer BTNEOx to the NC matrix which improve the normal distribution of the effective activation energy during each a that gives a homogeneous burning for the new propellants formula.…”
Section: Kissingeràakahiraàsunose (Kas) Methodsmentioning
confidence: 99%
“…Usually, thermal analysis is considered the best process of studying the thermal decomposition of energetic materials. The most common thermal analysis techniques such as thermogravimetric analysis (TGA), differential thermal analysis (DTA) and differential scanning calorimetry (DSC) have been used isothermally and non-isothermally in the study of the decomposition kinetics [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a thermoanalytical study of these PBXs was conducted by Yan et al [17][18][19] The penetration performance of the advanced nitramines has been studied, [20][21][22] while different relationships have been presented and discussed by Zeman et al [23][24][25][26] based on the reactivity and sensitivity of the studied PBXs. BCHMX as part of a low sensitivity composition was studied by Hussein et al [27][28][29] From the previously mentioned research, it was concluded that the polymeric matrices have a signicant inuence on the different explosive properties of the studied PBXs.…”
Section: Introductionmentioning
confidence: 99%